Characterization of Minerals, Metals, and Materials 2019 - Li, Bowen; Li, Jian.; Ikhmayies, Shadia; Zhang, Mingming; Kalay, Yunus Eren.; Carpenter, John S.; Hwang, Jiann-Yang.; Monteiro, Sergio Neves; Bai, Chenguang; Escobedo-Diaz, Juan P.; Spena, Pasquale Russo; Goswami, Ramasis; et al. (Cham : Springer International Publishing : Imprint: Springer, 2019)
This volume is focused on the advancements of characterization of various minerals, metals, and materials from bulk scale to nanoscale, and on the applications of characterization results on the processing of these materials. Topics include extraction and processing of various minerals, and the process-structure-property relationship of metal alloys, glasses and ceramics, polymers, composites, and carbon used as functional and structural materials. Advanced methodology and instrumentation for materials characterization are emphasized. The collection provides up-to-date achievements on many types of materials for the scientists and engineers engaged in research, development, and production. .
Part 1. Characterization Methods -- On FIB Milling Parameters -- Part 2. Characterization of Ceramics -- Preparation and Characteristics of Steel Slag Ceramics from Converter Slag -- In-situ XRD Investigation of Bauxite Dehydroxylation -- The Investigation of Humics as a Binder for LiFePO4 Cathode Using in Lithium Ion Battery -- Evaluation of Brazilian Bentonite Modified by Acid Attack in Biofuel Production -- Part 3. Characterization of Non-ferrous Metals -- Synthesis and Characterization on Nickel Orthosilicate Anode of Lithium-ion Battery -- Eletrochemical Behavior and Corrosion Properties of Ti-6Al-4V Alloy Made by Selective Laser Melting for Immersion in Artificial Seawater at Different Temperature -- Part 4. Microstructure and Performance of Materials -- Correlation of Microstructure to Dynamic Properties in Two Grades of Alumina -- Part 5. Characterization and Uses of Metallurgical Slags -- Preparation and Characterization of NaNO3/BFS Composite Phase Change Materials -- Characteristics of WISCO Steelmaking Slags -- Effects of Civil Construction Waste on Properties of Lining Mortars -- Pilot Trial of Direct Modification of Molten Blast Furnace Slag and Production of High Acidity Coefficient Slag Wool Fibers -- Reduction Behavior of Ternary Calcium Ferrites for CaO-Fe2O3-MgO System -- Propagation of Power Ultrasound in Calcium Ferrite Melt -- Part 6. Characterization of Polymer and Composite Materials -- Dynamic-mechanical Analysis of Epoxy Composites Reinforced with PALF Fibers -- Characterization of PCBs from Obsolete Computers Aiming the Recovery of Precious Metals -- IZOD Impact Test Comparative Analyzis of Epoxy and Polyester Matrix Composites Reinforced with Hemp Fibers -- Effect of Neomycin in PVP Hydrogel as Wound Dressing -- Comparative Mechanical Analysis of Epoxy Composite Reinforced with Malva/Jute Hybrid Fabric by Izod and Charpy Impact Test -- Comparison Between Epoxy Matrix Composites Reinforced with Ramie Fabric under Pressure and Vacuum -- Charpy Impact Test in Polyester Matrix Composites Reinforced With Hybrid Blanket of the Jute and Malva Fibers -- Part 7. Analysis of Surfaces and Interfaces -- Applications of Aberration-corrected Low-energy Electron Microscopy for Metal Surfaces -- ZnO Thin Films of Flowered-Fibrous Micro/Nanowebs on Glass Substrates Using the Spray Pyrolysis Method -- Intergranular Cracking of High Strength Alloyed Brass Rods -- Part 8. Mechanical Behaviors of Materials -- Determination of Microstructure-based Constitutive Models Using Temperature Rise Distribution in Plane Strain Machining -- Precipitating Behaviour of Second Phase Particles in Lightweight Fe-Mn-Al-C-N Stainless Steel -- Local Texture Evolution and Mechanical Performance of Ultra-High-Speed Friction Stir Weld of AA 6111-T4 sheets -- Part 9. Characterization of Powder Materials -- Characterization of HPGR Pre-treated Sinter Feed -- Thermogravimetric Analysis on Reduction Behavior of Powdery Dicalcium Ferrite -- Study on Application of Iron Ore Fine in Pelletizing -- Characterization of Different Clays for the Optimization of Mixtures for the Production of Ceramic Artifacts -- Part 10. Mineral Processing and Analysis -- Structural, Spectroscopic, Magnetic, and Thermal Characterizations of a Magnetite Ore from the Nagaland Region, India -- Humic Acid-based Silica Composite Aerogels--A Preliminary Study -- Characterization of Non-covalently Functionalized Halloysite -- Synchrotron-based XRD and XANES Study of Bornite Leached by Mesophilic Mixed Bacteria -- Adsorption and Surface Area of Bentonite Modified Used as Bleaching Clay -- Investigation for Removal of Organic Carbon from Carbonaceous Copper Sulphide Ore and Improving the Recovery of Copper through Flotation -- Part 11. Nanostructure and Characterization of Materials -- Microwave Synthesis of Co-Ni Ferrite/Graphene Nanocomposite for Microwave Absorption -- Evaluation of Urea Encapsulation by Microcapsules of PHB/MMT and PHB/OMMT Nanocomposites -- Part 12. Thermal Processing and Analysis -- Buildup Formation Mechanism of Carbon Sleeve in Continuous Annealing Furnace for Silicon Steel -- Pulse Parameter Characterization in Microdrilling of Maraging Steel 300 Alloy -- Characterization of Coke-making Coals of High Reactivity from Northwest China -- The Anodic Behavior of Electro-Deoxidation of Titanium Dioxide in Calcium Chloride Molten Salt -- Part 13. Poster Session -- Addition of Dregs in Mixed Mortar: Evaluation of Physical and Mechanical Properties -- Adhesion Study at Advanced Ages in Multipurpose Mortars -- Applications and Opportunities of Nanomaterials in Construction and Infrastructure -- Automated Optical Serial Sectioning Analysis of Phases in a Medium Carbon Steel -- Characterization of a Brazilian Bentonite for its Use in the Oil and Gas Industry -- Characterization of Tensile Properties of Epoxy Matrix Composites Reinforced with Fique Fabric Fiber -- Clay Smectite Synthetic: Characterization and Application in Nanocomposites -- Comparison of Performance between Granite Waste Pigments Based Paints and Soils Pigments Based Paints -- Development and Characterization of Recycled-HDPE/EVA Foam Reinforced with Babassu Coconut Epicarp Fiber Residues -- Evaluation of Microcapsules of PBSL/MMT-K and PBSL/OMMT-K Nanocomposites -- Evaluation of the Quality of Concrete with Waste of Construction and Demolition -- Evaluation of Two Different Pulsed Plasma Nitriding Conditions on Steel Properties -- Flexural Mechanical Characterization of Polyester Composites Reinforced with Jute Fabric -- Influence of Coupling Agent on the Modification Effects of Vanadium Tailing as a Polymer Filler -- Influence of Electron-beam Irradiation on the Properties of LDPE/EDPM Blend Foams -- Influence of the Areal Density of Layers in the Ballistic Response of a Multilayered Armor System Using Box-behnken Statistical Design -- Influence of the Blocks and Mortar's Compressive Strength on the Flexural Bond Strength of Concrete Masonry -- Influence of Two Solubilization Conditions at 718 Superalloy Hardness and Microstructure -- Irradiation Influence on the Properties of HMS-Polypropylene Clay/AgNPs Nanocomposites -- Limit Speed Analysis and Absorbed Energy in Multilayer Armor with Epoxy Composite Reinforced with Mallow Fibers and Mallow and Jute Hybrid Fabric -- Mechanical, Thermal and Electrical Properties of Polymer (Ethylene Terephthalate - PET) Filled with Carbon Black -- Mineralogical Analysis of A Chrome Ore from South Africa -- Pilot Trial of Detoxification of Chromium Slag in Cyclone Furnace and Preparation of Glass-ceramics with the water-quenched melt -- Preparation of Refractory Material from Ferronickel Slag -- Process Improvement Study on the Gradation Uniformity of Steel Slag Asphalt Concrete Aggregate -- Research on the Interaction of Humic Acid with Iron Minerals -- Study of Different Process Additives Applied to Polypropylene -- Study of the Durability of Mortars with Effluent Sludge from Paper Industry Exposed to Salt Spray -- Study of the Incorporation of Residue of Ornamental Rocks in Ceramic Tiles -- Study of the Incorporation of Smectite in Powder Coating -- Study of the Mineralogical Composition of the Tailings of Coscotitlán, Hidalgo, Mexico -- The Influence of Clay Reinforcement on the Properties of Recycled Polymer Foams -- The Quality of Tiles in Red Ceramic in Northwest of Rio de Janeiro and Southeast of Minas Gerais.
Keywords: Materials -- Analysis; Building materials; Materials; Characterization and Analytical Technique; Structural Materials; Materials Engineering